-x-2y+z=-6

Simple and best practice solution for -x-2y+z=-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -x-2y+z=-6 equation:


Simplifying
-1x + -2y + z = -6

Solving
-1x + -2y + z = -6

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2y' to each side of the equation.
-1x + -2y + 2y + z = -6 + 2y

Combine like terms: -2y + 2y = 0
-1x + 0 + z = -6 + 2y
-1x + z = -6 + 2y

Add '-1z' to each side of the equation.
-1x + z + -1z = -6 + 2y + -1z

Combine like terms: z + -1z = 0
-1x + 0 = -6 + 2y + -1z
-1x = -6 + 2y + -1z

Divide each side by '-1'.
x = 6 + -2y + z

Simplifying
x = 6 + -2y + z

See similar equations:

| 3x/7-5=4 | | 9(x-1)+3x=-9x+5 | | 2x+4y-2z=6 | | 0.42x-5=4 | | x+3y-z=12 | | 5x-y+5z=30 | | 5x-2x+6-4+14=5x-3x+8 | | 3(g-7)-2=4 | | 16=-4-4x | | -x+2y-3z=-9 | | -3t+5=26 | | 4x-2x+3-8=7x-5+4x | | 3t+5=26 | | (x^2+y^4)(x^2-y^4)=0 | | 0.67x+7=21 | | 72+36=0 | | 5x-2+8=7x-4 | | 21=8x-75 | | 6a+5x=36 | | (4s+4)(4s-4)=0 | | 3x+y+z=14 | | (3r-1)(4r-3)=0 | | 15-8m=73 | | -8x+6x-7x=3x(4-3)-5x-15 | | 98p=197 | | 5/3= | | 170-2x=25x+20 | | -5=15+4x | | 5x-x+3=-x+7 | | 5-9x=37-16x | | 3n+4=56 | | 3(4i)+2(7i)= |

Equations solver categories